Nursing Care for Diabetic Ulcer Clients Treated at Kabanjahe Regional Hospital - Juli Evianna Br. Purba; Miftahul Jannah (Jurnal Kesehatan Amanah, 2024)
Diabetic ulcers are defined as erosion of the skin that extends from the dermis to deeper tissues, due to various factors and is characterized by the inability of the injured tissue to repair itself in a timely manner, resulting in damage to the integrity of the patient's skin. What can be done is to close the wound, closing the wound is an important way to prevent infection and moisture. Removing the wound and minimizing the possibility of bacterial infection can also help speed up the healing process. This study aims to obtain an overview of nursing care for clients with diabetic ulcers at Kabanjahe Regional Hospital, North Sumatra. This study uses a literature review method with a Nursing Care approach by taking one case as a unit of analysis. The unit of analysis is a client with diabetic ulcers. The data collection method is by interview, physical examination and supporting examination. The data collection instrument uses the Nursing Care format according to the provisions in force in the Arta Kabanjahe nursing study program. Based on data analysis, it was concluded that the assessment requires effective communication skills, nursing diagnoses are adjusted to the client's condition, planning and implementation are supported by supporting facilities and means, evaluations are carried out directly, both formative and summative. In client 1, 5 diagnoses were obtained, 3 diagnoses were not resolved and 2 diagnoses were resolved. In client 2, 4 diagnoses were obtained, 2 diagnoses were resolved.